2014
DOI: 10.7314/apjcp.2014.15.17.7029
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Burden in Different Cancers in Iran: a Systematic Assessment

Abstract: Certain types of human papillomaviruses (HPVs) are undoubtedly involved in genesis of human malignancies. HPV plays an etiological role in cervical cancer, but also in many vaginal, vulvar, anal and penile cancers, as well as head and neck cancers. In addition, a number of non-malignant diseases such as genital warts and recurrent respiratory papillomatosis are attributable to HPV. Moreover, HPV forms have detected in several other cancers including esophageal squamous cell carcinoma, lung, prostate, ovarian, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
5
31
0
Order By: Relevance
“…HPV vaccine is developed for the prevention of cervical cancer in some countries. If HPV infection is associated with the risk of prostate cancer, it all cancers (6). In the present study, the majority of histological type of prostate cancer was adenocarcinoma.…”
Section: Discussionsupporting
confidence: 46%
“…HPV vaccine is developed for the prevention of cervical cancer in some countries. If HPV infection is associated with the risk of prostate cancer, it all cancers (6). In the present study, the majority of histological type of prostate cancer was adenocarcinoma.…”
Section: Discussionsupporting
confidence: 46%
“…In line with our study, the most frequently found HPVs in cervical carcinoma cases were HPV16 (accounting for over 50%) and HPV18 (12%) in numerous reports [24] . Mahmoudi et al [25] studied the role of HPV genotypes in cervical cancer in Yazd, Iran, and observed a high frequency of HPV16 (70%) and HPV18 (16.7%), followed by types 33, 45, and 73, respectively 41 [26] . These findings are consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…The average global prevalence of HPV infection has been reported to be almost 10% (in the range of 1.4-25.6%). This group of viruses consists of low-risk HPVs that do not cause cancer but can cause skin warts (genotypes 6, 11, 42, and 44), and high-risk HPVs that cause cancer (genotypes 16,18,26,31,33,35,39,45, 51, 52, 53, 56, 58, 59, 66, 68, 73, 82). Neoplastic and cervical cancer may occur due to exposure to high-risk HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Major high risk HPV subtypes reported in neighbouring countries such as Saudi Arabia include: HPV 11,33,31,39, 45, 51, 52, 53, 58, 59, 66, 68 and 73 28. HPV subtypes reported in Iran include;HPV 6, 11,31,33,35,39,42, 43, 44, 45,51, 52, 56, 58, 59, 66 and 68.…”
mentioning
confidence: 99%